Analisis Peranan Human Capital Management (HCM) Dalam Meningkatkan Pengembangan Sumber Daya Manusia (Studi Kasus : PT Enjiniring Pilar Cakrawala) - Fitri Khoerunnisa (Pusat Riset dan Inovasi Nasional, 2025)
This research aims to examine the role of Human Capital Management (HCM) in the development of human resources at PT. Enjiniring Pilar Cakrawala. The study is motivated by the critical importance of human capital—including employees’ knowledge, skills, and experience—as a strategic asset for companies navigating the increasingly competitive and complex engineering and construction sectors. A qualitative approach with a case study method was adopted, utilizing data gathered through in-depth interviews, participant observation, and documentation review. The findings reveal that HCM practices at PT. Enjiniring Pilar Cakrawala include technical and soft skills training, support for further education and professional certification, performance evaluation based on Key Performance Indicators (KPI), as well as structured career planning and succession programs. Elements such as employee knowledge, skills, experience, and HR development initiatives are shown to significantly enhance employee competencies, motivation, and productivity. Moreover, the company’s efforts to promote work-life balance and career advancement contribute positively to employee loyalty and retention. Overall, the study highlights that a well-structured and sustainable Human Capital Management strategy is essential for fostering effective human resource development and for maintaining the company’s competitiveness and long-term growth in the engineering consulting industry.